2017
DOI: 10.1371/journal.pntd.0005446
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effectiveness of weekly iron-folic acid supplementation and regular deworming over 6 years in women in rural Vietnam

Abstract: BackgroundWeekly iron-folic acid (IFA) supplementation and regular deworming is effective for the prevention of iron deficiency and anaemia in women of child-bearing age. Between 2006 and 2013, a program of weekly IFA and biannual deworming was implemented in Yen Bai province, Vietnam. In this study we aimed to determine the effectiveness of the program in reducing anaemia and the prevalence of hookworm infection after 72 months (six years).MethodsThis prospective cohort study followed up a cohort of 389 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 17 publications
2
25
0
2
Order By: Relevance
“…In conclusion, the present study showed that the STH epidemiological situation in Bhutan with an initially high STH endemicity and after establishing a successful STH control programme, infection saw decline. A similar decline has been observed in several other countries like Sri Lanka [32], Nepal [20], Afghanistan [33], Vietnam [34], Myanmar [35] and Lao PDR [36]. WHO estimated that preventive chemotherapy intervention will globally avert in children over 900000 Disability Adjusted Life Years(DALYs) in 2020 [37].…”
Section: Resultssupporting
confidence: 56%
“…In conclusion, the present study showed that the STH epidemiological situation in Bhutan with an initially high STH endemicity and after establishing a successful STH control programme, infection saw decline. A similar decline has been observed in several other countries like Sri Lanka [32], Nepal [20], Afghanistan [33], Vietnam [34], Myanmar [35] and Lao PDR [36]. WHO estimated that preventive chemotherapy intervention will globally avert in children over 900000 Disability Adjusted Life Years(DALYs) in 2020 [37].…”
Section: Resultssupporting
confidence: 56%
“…At the end of six years, 72.0 percent of participants reported still taking at least 75 percent of the weekly supplements, and 85.0 percent had taken the most recent deworming treatment. The results were dramatic; anemia fell from 37.8 percent to 14.3 percent, and hookworm prevalence dropped from 75.9 percent to 10.2 percent (Casey et al 2017). Although the cost per person was low ($0.76 per woman per year), the cost to the province of supplying weekly supplements ran as high as $200,000 a year-well beyond the provincial budget.…”
Section: Trials Of Weekly Iron and Folate For Adolescent Girlsmentioning
confidence: 98%
“…19 Sebuah hasil penelitian di Vietnam dimana pemberian obat cacing 2 kali setahun berhasil menurunkan prevalensi STH dari 83,7% menjadi 13,9% dalam kurun waktu 72 bulan/3 tahun. 21 Kegiatan intervensi, preventif dan promotif kecacingan berbasis sekolah dinyatakan efektif dan efisien baik dari sisi biaya maupun kesuksesan pengobatan karena adanya daya dukung dari pihak sekolah yang disegani oleh siswa. 11,22 Akan tetapi, tidak mengabaikan pula pentingnya intervensi, preventif dan promotif di lingkungan masyarakat umum atau di lingkungan desa khususnya lingkungan keluarga.…”
Section: Pendahuluanunclassified